China in Terms of Exchange Rate, Inflation and Interest Rate (Based on Database 2018) - Betrix Silitonga; Halimah Cahyaning Fajri; Trian Hutaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research model looks at the long-term relationship between exchange rates, interest rates, and inflation using Autoregressive Distributed Lag (ARDL) co-integration analysis based on database 2018. This study aims to ensure stability in the exchange regime through the structurally nexus of interest rates and inflation volatility and its targets. The data used is historical data on the country of China from 1987-2017. The results of the estimates show that inflation and interest rates in the previous period had a significant effect on the movement of the Chinese exchange rate, while the movement of the exchange rate of the previous period did not affect the movement of the exchange rate of the next period. Although there is a long-term cointegration between the independent variables, namely interest rates and inflation (CPI) against the dependent variables i.e. exchange rates, the long-term relationship between independent variables does not significantly affect the dependent variables.